On the Effect of Location Uncertainty in Spatial Querying - Frentzos, E.; Gratsias, K.; Theodoridis, Y. (IEEE transactions on knowledge and data engineering, 2009)
An emerging topic in the field of spatial data management is the handling of location uncertainty of spatial objects, mainly due to inaccurate measurements. The literature on location uncertainty so far has focused on modifying traditional spatial search algorithms in order to handle the impact of objects' location uncertainty in query results. In this paper, we present the first, to the best of our knowledge, theoretical analysis that estimates the average number of false hits introduced in the results of rectangular range queries in the case of data points uniformly distributed in 2D space. Then, we relax the original distribution assumptions showing how to deal with arbitrarily distributed data points and more realistic location uncertainty distributions. The accuracy of the results of our analytical approach is demonstrated through an extensive experimental study using various synthetic and real datasets. Our proposal can be directly employed in spatial database systems in order to provide users with the accuracy of spatial query results based only on known dataset and query parameters.